Opportunities and challenges of public relations in Yogyakarta special region high prosecutor’s office - Widianto, Eko; Rahmanto, Andre; Pawito, FNU (Universitas Padjadjaran, 2024)
Background: The High Prosecutor’s Office for Yogyakarta Special Region (D.I.Y., abbreviation in Indonesia) conducts public relations through the Legal Information Section (Penkum., acronym in Indonesia). Penkum communicates and listens to public opinion and builds and maintains the institution’s image. Purpose: This study aims to find out the communication strategies employed by Penkum and its public relations opportunities and challenges. Methods: The current research used the four-step theory of the public relations process by Cutlip, Center, and Broom to see whether the communication process by Penkum had gone through the stages of mapping the situation and strategy, conducting program planning, program execution, and evaluation. Then, it used the SWOT concept to reveal internal and external factors that become opportunities and challenges in running public relations programs. It used a qualitative descriptive approach to examine and understand the data collected through interviews with relevant officials. Results: The results of the data analysis found empirically that the communication strategy of Penkum as public relations has adopted public relations stages by mapping budget availability, program planning, program execution, and evaluation. The SWOT analysis obtained opportunities and challenges encountered in the public relations programs, including strength-opportunity strategy; weakness-opportunity strategy; strength-threat strategy; and weakness-threat strategy. Conclusion: Based on the four-step theory of public relations process and SWOT Analysis, this research recommends that the public relations at the High Prosecutor’s Office of D.I.Y: 1) increased programs that involve the community; 2) established an SOP for handling issues; 3) strengthened collaboration with the mass media; 4) added and update of public relations facilities and infrastructure; 5) improved the ability and skills of personnel. Implication: The findings in this study are expected to strengthen the public relations role of the Public Prosecutor’s Office and become a source for further related research.